1991
DOI: 10.1115/1.2891229
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineering in Development of the Hybrid Artificial Pancreas

Abstract: The hybrid artificial pancreas for treatment of diabetes consists of insulin-secreting pancreatic tissue which is surrounded by a membrane that protects the tissue from rejection by the immune system following implantation. In this paper, we review the alternative therapeutic approaches for diabetes under study and then discuss the technical requirements that must be met by a hybrid device useful to humans. Previous work on intravascular and extravascular immunoisolation devices is reviewed from the standpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
93
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(96 citation statements)
references
References 0 publications
1
93
0
Order By: Relevance
“…This approach was found to be rather successful because these devices implanted as high flow arteriovenous fistulas could remain patent for periods of 7 weeks in the absence of systemic anticoagulant therapy [12]. This success can be explained in part by the high flow rates through the device which prevents adhesion of cells to the membranes or collection of those cells in the immediate vicinity [13]. However, high flow arteriovenous fistulas are not without risk and much longer patency rates are required for effective applicability.…”
Section: Macroencapsulation Of Pancreatic Isletsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach was found to be rather successful because these devices implanted as high flow arteriovenous fistulas could remain patent for periods of 7 weeks in the absence of systemic anticoagulant therapy [12]. This success can be explained in part by the high flow rates through the device which prevents adhesion of cells to the membranes or collection of those cells in the immediate vicinity [13]. However, high flow arteriovenous fistulas are not without risk and much longer patency rates are required for effective applicability.…”
Section: Macroencapsulation Of Pancreatic Isletsmentioning
confidence: 99%
“…The hollow fibre geometry is usually preferred over the planar membranes for their smaller foreign body response [30]. Most studies on hollow fibres use fibres made of PAN-PVC [13,31], similar to those used in intravascular devices. They have been produced with a smooth and fenestrated outer skin with the same spongy matrix as applied in the intravascular.…”
Section: Macroencapsulation Of Pancreatic Isletsmentioning
confidence: 99%
“…It is realized that suf®cient diffusion of insulin and simultaneous blockage of IgG is not a trivial parameter in the design of a successful biocapsule membrane. Although the IgG molecule has a molecular weight of approximately 150 kDa, studies have disagreed on the actual dimensions of the molecule, estimated to be tens of nanometers or less [20,21]. For example, Wang et al [22] investigated permeability of relevant immune molecules to sodium alginate/poly-L-lysine capsules and found that signi®cant amounts of IgG (close to 40%) passed through both 230 and 110 kDa membranes in 24 h.…”
Section: Discussionmentioning
confidence: 99%
“…Some substances like transferrin may even be retained as the consequence of its incompatible conformation or its large molecular weight. Furthermore, the low oxygen tension [36][37][38] and low concentrations of essential minerals [36][37][38][39] in the peritoneal fluid may also contribute to a gradual decrease of the size of the islet graft and, therefore, limit the lifespan of the graft. The significance of the lack of vascular access for the viability of the encapsulated islets and for the occurrence of graft failure is illustrated by our observations that the diameters of encapsulated islets become smaller with time and that islets gradually develop necrotic zones.…”
Section: Discussionmentioning
confidence: 99%